Job satisfaction and its impact on employee performance - Al-Maaitah, Abdullah Khaled Salim (Journal of Economic, Administrative and Legal Sciences, 2017)
This study aims to try to identify the effect of job satisfaction on the performance of employees in the Jordanian Phosphate Mines Company Ltd (JPMC),it investigates the effects of salaries, incentives, bonuses, relationship with immediate supervisor, colleagues, work environment, justice, and some personal characteristics such as gender, age, marital status, experiences and academic qualifications on job satisfaction ,The study descriptive analytical methods to arrive at results, the SPSS was used to process the available data A questionnaire was adopted to achieve the purposes of this study and test its hypotheses the study which included 227 participants found out some results as :The findings show that the degree of job satisfaction at the JPMC is moderate with a statistical significance of 3.11 which demonstrates a moderate degree of satisfaction and There is Positive correlation between the degree of job satisfaction and their performances at JPMC ,and The degree of job satisfaction pertaining to salaries, incentives and bonuses affects employees performance at the JPMC Based on the result , the study arrived at the following : The importance of linking incentives and salaries to the current increase in prices and Paying more attention to the employees suggestions. And Involving employees in courses and seminars.